Analysis of Axin2 expression and function in murine models for pancreatic cancer. Issue 1 (December 2016) - Zechner, Dietmar; Kroemer, Tim; Albert, Ann-Christin; Schönrogge, Maria; Radecke, Tobias; Vollmar, Brigitte
Abstract Background The involvement of Wnt in carcinogenesis and progression of pancreatic cancer is currently intensely discussed. We evaluated activation of the Wnt signaling pathway by using a Wnt reporter mouse strain expressing β-galactosidase under the control of the Axin2 promotor during pancreatitis induced formation of precancerous lesions. We also evaluated activation of Wnt signaling during interaction of pancreatic cancer with the tumor stroma. Results Activation of Wnt signaling was observed during acinar-to-ductal metaplasia after chronic as well as acute pancreatitis. Activation of Wnt signaling was also noticed during growth of pancreatic cancer in an orthotopic syngeneic pancreas cancer model. Activation of Wnt signaling was, however, not observed in carcinoma associated fibroblasts, but was detected in few cell clusters inside the tumor. Genetic ablation of Axin2 significantly reduced body weight without having a major impact on blood glucose concentration. However, ablation of Axin2 had no influence on the observed β-galactosidase positive cell clusters or on tumor weight. Conclusion These data demonstrate that the Wnt signaling pathway is activated during acinar-to-ductal metaplasia after injury to the pancreas. However these data do not support a major role of Wnt signaling or of Axin2 in carcinoma associated fibroblasts and tumor growth.